Silver electrode as a sensor for determination of zinc in cell cultivation medium - Kizek, René; Trnková, Libuse; Sevcíková, Sabina; Smarda, Jan; Jelen, Frantisek (Analytical biochemistry, 2002)
Use of the silver electrode as a sensor for the monitoring of zinc in cell growth medium is described. Zinc at silver electrodes provides specific voltammetric signal, which is affected by solution components. Signals of zinc ions in phosphate buffer solutions with and without cell growth medium were compared. Common DMEM cell culture medium was used for the cultivation of a cell line of v-myb-transformed chicken monoblasts and its variants expressing v-jun and c-jun in a zinc-dependent manner. Electrochemical results showed zinc concentrations in the medium coincide very well with the jun expression. With respect to the low toxicity of silver for eukaryotic cells, silver electrodes represent promising tools for the determination of zinc concentrations in vivo without the potential risk of a cell culture damage.
Keywords: iontově selektivní elektrody; metalothionein; kur domácí; Animals; Metallothionein; Chickens; Silver; onkogenní protein p65(gag-jun); Oncogene Protein p65(gag-jun); Cell Line, Transformed; Zinc; Culture Media; transformace genetická; zinek; geny myb; kultivační média; Transformation, Genetic; Genes, myb; promotorové oblasti (genetika); zvířata; Promoter Regions, Genetic; transformované buněčné linie; Ion-Selective Electrodes; stříbro